Quo Vadis Penelitian Pendidikan Agama Kristen di Indonesia - Majesty, Gilbert Timothy; A Dan Kia (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Christian Religious Education (PAK) research in Indonesia has undergone significant developments, but its future direction and relevance are still crucial questions. This article aims to map the PAK research landscape and identify key challenges and opportunities through a literature review of publications in national and international journals, theses, and dissertations. The analysis is focused on three aspects: dominant themes, methodology, and contextual relevance. The findings show the dominance of conventional themes such as teaching methods, curriculum, and the role of teachers, with a qualitative approach limited to case studies, making generalizations difficult. Contemporary issues such as religious pluralism, digital media, Generation Z spirituality, integration of faith and knowledge, and inclusive approaches in multicultural contexts are still underexplored. This article proposes the reorientation of PAK research through an interdisciplinary approach (theology with psychology, sociology, media studies), methodological strengthening (longitudinal and mixed-methods studies), and emphasis on Indonesia's socio-cultural reality as a starting point. With this strategy, PAK's research is expected to be able to expand its theoretical contribution while answering practical challenges in shaping the character and spirituality of students in the era of modernity.